Analysis of Trends in Food Crop Production in West Sumatra Province - Andreas Sitanggang (Journal of Agribusiness and Natural Resources, 2025)
Food crops are agricultural commodities that have a significant contribution to food security, economic stability, and community welfare. West Sumatra Province, as one of the agricultural regions in Indonesia, has great potential in developing various food crop commodities that are an important part of people's consumption and life. Despite having the potential to support natural resources, the dynamics of food crop production in West Sumatra show fluctuations from time to time. Analysis of food crop production trends is important to understand production development patterns and identify challenges and opportunities in efforts to increase food crop commodity production. This study aims to determine the trend in the amount of food crop commodity production in West Sumatra Province. This study analyzed food crop production trends in West Sumatra Province using quantitative descriptive analysis of secondary data from the Central Statistics Agency (2020-2024). Six commodities were examined: paddy, corn, peanuts, mung beans, cassava, and sweet potatoes. The results of the study found that throughout 2018-2024, the production of food crop commodities in West Sumatra Province, consisting of paddy, corn, peanuts, mung beans, cassava, and sweet potatoes, showed a negative trend where food crop commodities tended to experience a decrease in production from year to year. The production of food crop commodities is influenced by various factors, including land area, seeds, fertilizers, pesticides, the number of workers, and climate change. The declining food crop production in West Sumatra Province requires immediate attention to ensure food security amid growing population demands.